Middle facet tarsal coalition in a National Collegiate Athletic Association basketball athlete: An exploration clinical case report - Watts, M.; Sumrall, K. (International Journal of Athletic Therapy & Training, 2024)
The patient is a 22-year-old female basketball player initially diagnosed with a calcaneal fracture. Five months after the pain began, the patient was referred to a foot and ankle surgeon and diagnosed with middle facet tarsal coalition. The patient received one X-ray-guided subtalar steroid injection and two platelet-rich plasma injections to aid in pain relief while completing her senior year of collegiate basketball. She elected to end her senior season early to have the recommended subtalar fusion surgery. The surgery ended her basketball career but provided pain-free activities of daily living. This case presents unique components compared with available literature on how injury presentation in adult populations can complicate a timely and accurate initial diagnosis. This case is also unique because despite conservative efforts, a surgical fusion was required to optimize pain and function during activities of daily living.